Հարկային վարչարարության ձևավորման նախադրյալները - Անի Եգորի Հոսեփյան (ՀՀ ԳԱԱ հրատ.)
Статья посвящена направлениям формирования налогового администрирования В РА. В ней исследованы сущность налогового администрирования, особенности процесса управления налоговыми отношениями. The article describes the directions that the tax administration in the Republic of Armenia. The article studies the meaning of the tax administration, and characteristics of the process of managing tax relations.
Keywords: Հասարակական գիտություններ; Տնտեսագիտություն; Ֆինանսներ